Economic Valuation of Home Gardens of Wet Zone Low Country of Sri Lanka - Priyadarshika, G.D.S.; Gunawardena, U.A.D.P. (University of Sri Jayewardenepura, 2016)
Home gardens play an important role in household economy and are important ecosystems in the country. This study sought to estimate economic value of home gardens in the Wet Zone Low Country 3 agro ecological region (WL 3 AER) and intended to identify factors that contribute to the economic value. A structured questionnaire survey was conducted among randomly selected home gardens with varying sizes in Gampaha and Colombo districts. Information on size, crop types, yield and costs of inputs were collected along with respondents’ socio economic factors. Net average value of a home garden is LKR 76, 355 per annum while average value per hectare per annum is LKR 433,855. Values of each size category indicate an optimal size (perch 21-40) for maximum economic gains. Regression analysis indicates that an additional year of stay could increase the value by LKR 1245 and additional perch cultivated increase the value by LKR 500. The results highlighted the importance of home garden systems in the WL 3 AER for the household economy and the significance of recognizing that value in making decisions regarding home gardens.
Keywords: home gardens, economic value, low country, wet zone